2020
DOI: 10.1001/jamaoto.2019.3277
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Rate of Occult Contralateral Nodal Disease in Surgically Treated Patients With Human Papillomavirus−Related Squamous Cell Carcinoma of the Base of the Tongue

Abstract: IMPORTANCEThe optimal treatment strategy for patients with human papillomavirus (HPV)−related oropharyngeal squamous cell carcinoma (OPSCC) of the base of the tongue (BOT) has not been sufficiently studied.OBJECTIVE To investigate the rate of and risk factors for occult contralateral nodal disease in patients with HPV-related BOT OPSCC undergoing transoral surgery and bilateral neck dissections. DESIGN, SETTING, AND PARTICIPANTSThis retrospective case series reviewed the medical records of patients with HPV-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
23
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 21 publications
3
23
1
Order By: Relevance
“…In the recently published ORATOR trial, which randomized early‐stage OPSCCs to definitive radiation protocols or definitive surgery with guideline‐based adjuvant treatment, 88% of which were HPV+OPSCC, the recurrence rate (12%), progression‐free survival (PFS; >85%), and OS (>90%) were similar in the 2 arms of the trial and similar to those for our patient cohort treated with surgery alone 23 . Compared with the less than 2% rate of contralateral neck recurrence in our highly selected cohort, the rates of contralateral LN metastases in other studies have been higher at 12% to 21% for patients with BOT HPV+OPSCC 36‐38 . However, these studies included patients with more advanced primary site and nodal disease, which could potentially lead to the higher rates of contralateral metastases.…”
Section: Discussionsupporting
confidence: 73%
“…In the recently published ORATOR trial, which randomized early‐stage OPSCCs to definitive radiation protocols or definitive surgery with guideline‐based adjuvant treatment, 88% of which were HPV+OPSCC, the recurrence rate (12%), progression‐free survival (PFS; >85%), and OS (>90%) were similar in the 2 arms of the trial and similar to those for our patient cohort treated with surgery alone 23 . Compared with the less than 2% rate of contralateral neck recurrence in our highly selected cohort, the rates of contralateral LN metastases in other studies have been higher at 12% to 21% for patients with BOT HPV+OPSCC 36‐38 . However, these studies included patients with more advanced primary site and nodal disease, which could potentially lead to the higher rates of contralateral metastases.…”
Section: Discussionsupporting
confidence: 73%
“…In addition, although all primary subsites were allowed in our study, perhaps due to a selection bias from the treating physicians, 90% of patients in our cohort had tonsillar cancers and only a minority were base of tongue or subsites considered to have bilateral drainage. In fact, the risk of contralateral occult disease with base of tongue tumors was recently reported to be high as 21% 38 . While coverage of level II‐III contralateral nodes with 43.2 Gy and concurrent chemotherapy could potentially sterilize occult, microscopic contralateral disease, the safety of our approach certainly requires further investigation for lesions approaching midline given their small representativity in the current study.…”
Section: Discussionmentioning
confidence: 80%
“…In fact, the risk of contralateral occult disease with base of tongue tumors was recently reported to be high as 21%. 38 While coverage of level II-III contralateral nodes with 43.2 Gy and concurrent chemotherapy could potentially sterilize occult, microscopic contralateral disease, the safety of our approach certainly requires further investigation for lesions approaching midline given their small representativity in the current study. While consensus guidelines recognize ipsilateral radiotherapy as a standard option for well lateralized T1N0-1 tonsillar tumors, 39 ipsilateral radiotherapy in more advanced regional disease remains a subject of debate.…”
Section: Discussionmentioning
confidence: 90%
“…This appears consistent with recent data from Last et al who reported almost all contralateral disease to be confined within Levels II and III. 2,3 Was a similar distribution found among the 11 patients with pCND in Smith et al's series? Furthermore, in their six cases where clinical staging predicted pCND, did clinical staging accurately predict the involved levels?…”
mentioning
confidence: 74%